Advokasi Partisipatoris Berbasis Media Visual bagi Warga Pesisir di Desa Timbulsloko Demak dalam Menghadapi Dampak Perubahan Iklim : Indonesia - Anisa , Dian Dwi; Nazaruddin, Muzayin; Habibi, Zaki (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
The climate crisis has seriously affected Indonesia's coastal areas, including Timbulsloko Village in Sayung Subdistrict, Demak. In this area, tidal flooding has submerged productive farmland and forced residents to adapt continuously. However, technical adaptation alone is insufficient; advocacy is also necessary to ensure community voices reach policymakers. This community-service program aimed to empower Timbulsloko residents in climate-crisis advocacy through photovoice training and the use of Instagram as a visual campaign platform. The program was implemented in partnership with Puspita Bahari, a community of women fishers in Demak, and involved participants from diverse age, gender, and occupational backgrounds. The methodology employed a participatory approach with three stages: (1) preparation, involving preliminary research, partner coordination, and training-of-trainers; (2) implementation of photovoice workshops; and (3) follow-up activities, comprising participants’ visual documentation via the Instagram account @timbulslokobangkit with ongoing support from the engagement team. Program outcomes included enhanced community capacity to document and visually communicate the impacts of the climate crisis; the creation of authentic campaigns reflecting the perspectives of affected communities; and strengthened collective awareness of environmental rights. A critical reflection from the program is its application of participatory action research principles in community engagement, including collaborative, social-process, emancipatory-critical, sustainability, and dialectical-reflective principles.